Europe and the Testimony of Edith Stein - Suchocka, Hanna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
This article, written from the legal and constitutional perspective, seeks to explore John Paul II’s reasons that made him announce Edith Stein the co-patroness of Europe. The author begins with recalling prior patrons of Europe that is Saint Benedict and Saint Cyril and Methodius, and juxtaposes it with further pope’s decision to add three saint women to them. It is also an occasion to discuss questions like: woman rights and request for their greater participation in the public sphere, the concept of ‘new feminism’, national and religious issues, ecumenical and interreligious dialogue, Judeo-Christian roots of the Europe, human rights and ‘civilisation of death’ – all related with Edith Stein. The last part of the article is devoted to the reflection on law: the natural and the so-called ‘good law’, as well as its establishment.